Self-sensing bionic dot array structure and preparation method and application thereof

CN123006731APending Publication Date: 2026-10-30XIDIAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611109766.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]但是,现有技术的点阵结构单元在压缩应力-应变过程中表现出明显的应力波动及不稳定的屈曲行为,无法有效抵抗实际工程应用中因应力的快速下降而导致的整体结构所发生的失效

Benefits of technology

1.本发明在传统BCC结构的基础上,通过深海玻璃海绵生物的生物层级结构特征,引入双对角增强支柱和SC支柱,实现了GSIBCC点阵结构机械性能的极大提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123006731A_ABST
    Figure CN123006731A_ABST
Patent Text Reader

Abstract

The application discloses a self-sensing bionic dot array structure and a preparation method and application thereof, takes a cubic dot array unit cell as a basic dot array structure unit, periodically array expands along orthogonal directions in space, and overall constitutes a dot array structure body. The dot array structure unit comprises an EXBCC double-diagonal reinforcing dot array unit and a GSIBCC glass sponge simulating dot array unit. The EXBCC double-diagonal reinforcing dot array unit comprises diagonal rod members connected on square frames on top and bottom surfaces of a normal cubic frame, cross rod members respectively connected with the diagonal rod members and outer frame rod members are arranged in the frame, short inclined rods are connected outside cross points of the diagonal rod members, and long inclined rods meet on nodes respectively connected with the outer frame rod members. The GSIBCC glass sponge simulating dot array unit is provided with central rod members distributed between long inclined rod meeting nodes and four cross rod meeting nodes. The structure has excellent elasticity, good energy absorption capacity and impact electrical sensing function, and remarkably improves the buffering and protection performance of equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of engineering material preparation and structural design technology, and in particular to a self-sensing biomimetic lattice structure, its preparation method, and its application. Background Technology

[0002] Three-dimensional biomimetic lattice structures are a new type of mechanical metamaterial in mechanical metamaterials. As shown in Figure 1(a)-(c), the traditional BCC lattice unit consists of 12 equal-length outer frame rods 1 forming all 12 edges of a cube, creating a regular cube frame. The side length of the outer frame rods 1 is L1. Inside the cube, there are four intersecting rods 2 with four opposite corners connected to each other and passing through the center of the cube.

[0003] Traditional three-dimensional biomimetic lattice structures composed of BCC lattice units have demonstrated unique advantages that are difficult to achieve with traditional materials due to their highly designable microstructure and structure-driven macroscopic mechanical properties. For example, honeycomb, skeleton, and nacre can achieve precise control over target functions to a large extent. Currently, existing lattice structures mostly focus on improving single properties, while research on the multifunctional integration of lattice structures is still insufficient. Combining lattice structures with functional materials possessing electrical response characteristics is one of the important ways to achieve structural multifunctionality. Electrical responses based on conductive fillers can generate measurable resistance changes during structural deformation under load, thereby enabling real-time sensing of the structural deformation state. This type of structure has a clear theoretical basis and engineering application value in the fields of health monitoring and intelligent protection.

[0004] However, existing lattice structural units exhibit significant stress fluctuations and unstable buckling behavior during compressive stress-strain processes, failing to effectively resist overall structural failure caused by rapid stress reduction in practical engineering applications. Furthermore, existing lattice structures primarily focus on improving single performance characteristics, with insufficient research into achieving a deep integration of mechanical protection and electrical sensing performance, making them ill-suited to the complex functional requirements of wearable protective equipment.

[0005] Combining lattice structures with functional materials possessing electrical responsiveness is one of the important ways to achieve multifunctional structures. Electrical responses based on conductive fillers can generate measurable resistance changes during structural deformation under load, thereby enabling real-time sensing of the structural deformation state. This type of structure has a clear theoretical basis and engineering application value in the fields of health monitoring and intelligent protection.

[0006] Therefore, how to integrate lattice structures into wearable protective equipment such as elbow pads to not only effectively improve the equipment's buffering and protective performance, but also to achieve real-time sensing and feedback of external impact loads has become a pressing technical problem that needs to be solved. Summary of the Invention

[0007] To address the aforementioned shortcomings in existing technologies, this invention aims to provide a self-sensing biomimetic lattice structure, its fabrication method, and its applications. This structure incorporates the biological hierarchical structural characteristics of a deep-sea glass sponge skeleton, and through synergistic design of relative density and offset coefficients, effectively enhances the structure's overall mechanical properties. Applying the uncured flexible conductive lattice structure to the protection of fragile devices and wearable impact protection demonstrates excellent elasticity, good energy absorption capacity, and impact sensing capabilities. It not only significantly improves the buffering and protective performance of equipment but also enables real-time sensing and feedback of external impact loads, achieving integrated buffering energy absorption and self-sensing monitoring functions.

[0008] The present invention is achieved through the following technical solution.

[0009] In one aspect, the present invention provides a self-sensing biomimetic lattice structure. The lattice structure uses cubic lattice units of their respective configurations as basic lattice structural units, and periodically expands them along the three orthogonal directions of space X, Y, and Z to form a lattice structure of the scale of M×N×P, where M≥1, N≥1, and P≥1. The lattice structure unit includes an EXBCC double diagonal reinforced lattice unit; the EXBCC double diagonal reinforced lattice unit includes a cubic frame composed of outer frame members, a pair of diagonal members connected to the square frames on the top and bottom surfaces of the cubic frame, and a pair of four intersecting members inside the cubic frame that respectively connect the pair of diagonal members and the outer frame members, the short diagonal members of the four intersecting members being connected to the intersection of the pair of diagonal members, and the long diagonal members of the four intersecting members converging at their respective nodes connected to the outer frame members.

[0010] Preferably, the intersecting members are four diagonal members distributed along the outer frame members. The intersecting members split into two independent intersecting nodes along the central intersection point, and the four intersecting members are bidirectionally symmetrically offset along the extension direction of the outer frame members.

[0011] Preferably, one end of the short diagonal bar of the four intersecting members is connected outside the intersection point of a pair of diagonal members, and the distance extended inward from the connection point relative to the vertex of the diagonal member is... L1, where L1 is the side length of outer frame member 1, m is the offset coefficient, 0 < m ≤ 1 / 2.

[0012] Preferably, one end of the four intersecting long diagonal members is connected to the longitudinal upright of the outer frame member, and the connection point is offset by a bidirectional symmetrical amount of mL1 relative to the vertex of the outer frame member, where L1 is the side length of the outer frame member 1, m is the offset coefficient, and 0 < m ≤ 1 / 2.

[0013] Preferably, the dot matrix structure unit includes a GSIBCC glass-like sponge dot matrix unit, wherein the GSIBCC glass-like sponge dot matrix unit has a central member distributed between the intersection node of the long diagonal bar of the EXBCC dot matrix unit and the intersection node of the four intersecting members.

[0014] In another aspect, the present invention provides a method for preparing the aforementioned self-sensing biomimetic lattice structure, comprising the following steps: (a) Photosensitive resin is selected as the molding material, photocuring molding process is adopted, surface projection photocuring 3D printing equipment is selected, and flexible LCD photosensitive resin is used for printing. (b) Following the preset three-dimensional model path, the double diagonal reinforced body-centered cubic lattice structure EXBC and the glass-like sponge body-centered cubic lattice structure GSIBCC are printed by setting parameters through layer-by-layer exposure and curing with ultraviolet light. (c) The obtained lattice structure was ultrasonically cleaned with anhydrous ethanol, cleaned with deionized water, dried and cured with ultraviolet light to obtain EXBCC or GSIBCC lattice structure. (d) The lattice structure is directly immersed in a carbon nanotube conductive solution, the whole structure is treated under vacuum conditions, and then the pressure is slowly released to atmospheric pressure; (e) The sample was left to stand in the carbon nanotube suspension for a while and then dried to obtain the EXBCC or GSIBCC self-sensing lattice structure.

[0015] Preferably, in step (a), the parameters are set as follows: layer height 30~50μm, exposure time 5~8s, bottom layer exposure 30~60s, lifting speed 50~80mm / min, lifting height 5~8mm, and printing is performed using flexible LCD photosensitive resin in an environment of 20℃~25℃.

[0016] Preferably, the carbon nanotube conductive solution is prepared according to the following method: A conductive solution was obtained by adding La33 aqueous binder to a single-walled carbon nanotube aqueous dispersion with a content of 0.4-0.5% at a mass ratio of (20-30):(0.1-0.3) and stirring the mixture for 6-10 hours.

[0017] Preferably, in step (c), the lattice structure is ultrasonically cleaned in 95% anhydrous ethanol for 15-30 min; and then cured in a UV curing chamber for 10-30 min. In step (d), the treatment is carried out under a vacuum of 0.08~0.09 MPa for 20~30 min; In step (e), the sample is left to stand in a carbon nanotube suspension for 2-5 hours and then dried at 50-60°C for 2-5 hours.

[0018] The present invention, by adopting the above technical solution, has the following beneficial effects: 1. Based on the traditional BCC structure, this invention introduces double diagonal reinforcing pillars and SC pillars by taking advantage of the biological hierarchical structural characteristics of deep-sea glass sponges, thereby greatly improving the mechanical properties of the GSIBCC lattice structure.

[0019] 2. By using relative density and offset coefficient as parametric design variables, target optimization methods can be used to achieve multiple performance improvements of lattice structures, increasing the design space for structural performance.

[0020] 3. Using flexible resin as the matrix material, the lattice structure can be immersed in a carbon nanotube dispersion to cover the conductive nanotube filler on the surface of the lattice structure matrix. Through the immersion in the carbon nanotube solution, the lattice structure can be given an additional electrical sensing function, realizing a dual function that combines mechanical load-bearing capacity, energy absorption buffering, and electrical sensing of external loads. This provides a brand-new multifunctional design concept for lattice structures in future health monitoring and intelligent protection.

[0021] 4. For lattice structures that have not undergone secondary curing, good elasticity can be maintained after impregnation with carbon nanotubes, and good recovery ability is observed at low frequencies. The lattice structure can not only effectively absorb external impact forces, but also sense changes in resistance through its deformation. The self-sensing biomimetic lattice structure of this invention can be applied to the protection of fragile devices and wearable protective equipment. Attached Figure Description

[0022] The accompanying drawings, which are included to provide a further understanding of the invention and form part of this application, do not constitute an undue limitation of the invention. In the drawings: Figure 1(a) is a schematic diagram of the traditional three-dimensional BCC structure; Figure 1(b) is a two-dimensional schematic diagram of the diagonal cross-section of BCC; Figure 1(c) is a schematic diagram of the three-dimensional lattice structure of BCC. Figure 2(a) is a schematic diagram of the three-dimensional structure of EXBCC; Figure 2(b) is a schematic diagram of the two-dimensional cross-section of EXBCC; Figure 2(c) is a schematic diagram of the three-dimensional lattice structure of EXBCC. Figure 3(a) is a schematic diagram of the three-dimensional structure of GSIBCC; Figure 3(b) is a schematic diagram of the two-dimensional cross-section of the diagonal of GSIBCC; Figure 3(c) is a schematic diagram of the three-dimensional lattice structure of GSIBCC. Figure 4 Comparison of compressive stress response and mechanical properties of BCC, OCT, GSIBCC (m=1 / 4), EXBCC-A (m=1 / 4), and EXBCC-B (m=1 / 2) lattices with a relative density of 0.078: Figure 4 (a) is the compressive stress-strain curve; Figure 4 (b) represents the yield strength; Figure 4 (c) represents the platform stress; Figure 4 (d) represents specific energy absorption; Figure 5 This is a sample of the lattice structure of the present invention. Figure 5 (a) is a set of lattice structure samples used for experiments; Figure 5 (b) shows the detailed structure of the BCC, OCT, EXBCC (m=1 / 4) and GSIBCC dot matrix; Figure 6 This is a schematic diagram of the manufacturing process of the structurally bonded carbon nanotubes of the present invention; Figure 7 This is a lattice sample impregnated with carbon nanotubes according to the present invention. Figure 7 (a) is a set of lattice structure samples used for experiments; Figure 7 (b) shows the detailed structure of the BCC, OCT, EXBCC (m=1 / 4) and GSIBCC dot matrix; Figure 8 This is a SEM image of the carbon nanotube coating sample of the present invention. Figure 8 (a) is 200um; Figure 8 (b) is 10µm; Figure 8 (c) is 2µm; Figure 8 (d) is 500 nm; Figure 9 This invention relates to the experimental application of the EXBCC (m=1 / 4) lattice structure under dynamic impact. Figure 9 (a) and (b) show the simulated impact test process of the car; Figure 9 (c) The collision result of the protective device equipped with an EXBCC (m=1 / 4) self-sensing dot matrix; Figure 9 (d) shows the results of the control group without the added lattice structure under the same impact; Figure 10 This invention relates to the instantaneous resistance change of the EXBCC (m=1 / 4) lattice structure during a vehicle impact. Figure 10 (a) shows the resistive response of the EXBCC (m=1 / 4) lattice structure during the first impact; Figure 10 (b) shows the resistive response of the lattice structure during the second impact; Figure 11 This invention relates to an experiment testing the energy absorption of free fall. Figure 11 (a) is a diagram of the experimental setup; Figure 11 (b) is a schematic diagram of the experimental results; Figure 11 (c) is a diagram of the experimental process; Figure 12 This invention relates to the application of the EXBCC (m=1 / 4) lattice structure in elbow pads. Figure 12 (a) is a schematic diagram of the elbow pad impacting the wall when it is embedded in the lattice structure; Figure 12 (b) shows the change in resistance curve under this impact condition. Detailed Implementation

[0023] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. The illustrative embodiments and descriptions of the present invention are used to explain the present invention, but are not intended to limit the present invention.

[0024] Referring to Figures 2(c) and 3(c), a self-sensing mechanical metamaterial lattice structure based on the layered characteristics of deep-sea glass sponge is provided for the embodiment of the present invention. Each skeletal lattice structure uses the cubic lattice unit cell of its own configuration as the basic structural unit, and periodically expands along the three orthogonal directions of space X, Y, and Z to form a lattice structure of the scale of M×N×P, where M≥1, N≥1, and P≥1.

[0025] To further illustrate the self-sensing mechanical metamaterial lattice structure of the deep-sea glass sponge layer characteristics of the present invention, a BCC structure is used as a comparative example.

[0026] Figure 2(a) shows the EXBCC double diagonal reinforced lattice unit with a lattice structure. The EXBCC double diagonal reinforced lattice unit includes a cubic frame composed of outer frame members 1. The 12 outer frame members 1 with a side length of L1 of BCC are completely preserved. The four intersecting members 2 that converge at the center of the cube are symmetrically offset in both directions along the direction of the outer frame members 1. The symmetrical offset of the four intersecting members 2 in both directions along the extension direction of the outer frame members 1 is mL1. L1 is the side length of the outer frame members 1, and m is the offset coefficient. The offset coefficient m is used to adjust the configuration of the GSIBCC lattice structure. The value range is 0 < m ≤ 1 / 2. Only when 0 < m < 1 / 2 does GSIBCC exhibit double diagonal reinforcement characteristics.

[0027] As shown in Figure 2(a), the original single central intersection point of the intersecting members 2 is split into two independent sets of intersection points. The four intersecting members 2 are symmetrically offset in both directions along the extension direction of the outer frame members 1. The internal diagonal members form a spatial configuration with double diagonal reinforcement. At the same time, a pair of diagonal members 3 are added inside the square frames on the upper and lower surfaces of the cube, and are arranged intersecting along the diagonals of the upper and lower square frame surfaces to form a surface reinforcement layer. That is, there is a pair of four intersecting members 2 inside the cube frame, which respectively connect a pair of diagonal members 3 and the outer frame members 1. The short diagonal members of the four intersecting members 2 are connected to the intersection point of the pair of diagonal members 3, and the long diagonal members of the four intersecting members 2 converge at the nodes that connect to the outer frame members 1.

[0028] Four intersecting members 2, with one end of a short diagonal member connected to the outside of the intersection point of a pair of diagonal members 3, extend inward from the connection point relative to the vertex of the diagonal member 3 by a distance of... L1. One end of the four intersecting members 2 long diagonal members is connected to the longitudinal upright of the outer frame member 1, and the connection point is offset by mL1 in both directions relative to the vertex of the outer frame member 1.

[0029] In another embodiment of the present invention, as shown in Figure 3(a), the GSIBCC imitation glass sponge lattice unit is based on the EXBCC structure. Specifically, a central member 4 is distributed between the intersection node of the long diagonal bar of the EXBCC lattice unit and the intersection node of a pair of four intersecting members 2, forming a cross-shaped support structure with mutual overlap.

[0030] Figures 1(b), 2(b), and 3(b) are front views of the vertical cross-sections of the upper and lower diagonals of the three lattice structural units, respectively. The EXBCC double diagonal reinforced lattice unit and the GSIBCC glass-like sponge lattice unit present the spatial position and offset of the internal diagonal rods in a two-dimensional projection.

[0031] like Figure 4 As shown, this paper compares the compressive mechanical responses of five lattice structures—BCC, OCT, GSIBCC (m=1 / 4), EXBCC-A, and EXBCC-B—under uniaxial compression testing. BCC and OCT are existing lattice structural units; EXBCC-A and EXBCC-B are lattice structural units under two extreme offset distances. EXBCC-A is a lattice structural unit with double diagonal reinforcing struts but no internal cross-shaped struts at m=1 / 4. EXBCC-B is a lattice structural unit with internal cross-shaped struts but no double diagonal reinforcing struts at m=1 / 2. The compressive stress evolution of these five lattice structures all exhibit three distinct stages: 1) the linear elastic stage, where stress increases linearly with strain; 2) the initial yield and plastic plateau stage, where stress changes with compressive strain; and 3) the densification stage, where stress rises rapidly with increasing strain. Figure 4In (a), the compressive stress-strain curves of BCC, OCT, and EXBCC-B (m=1 / 2) exhibit remarkably similar evolution trends with increasing strain. A significant peak stress is observed during the initial loading stage. Subsequently, the stress decreases sharply, and the compression curves show obvious stress fluctuations and unstable buckling behavior. The GSIBCC lattice structure, however, exhibits a completely different compressive stress response compared to the BCC, OCT, EXBCC-A, and EXBCC-B lattice structures. During the initial loading stage, the compressive stress begins to yield, and no significant peak stress is observed. Furthermore, unlike the significant decrease in stress during the compressive response of BCC, OCT, and EXBCC-B, the compressive stress of GSIBCC continues to increase after initial yielding. This continuous increase in stress during compression implies that GSIBCC is inherently superior to BCC and OCT. As the compressive strain further increases, GSIBCC exhibits a relatively stable stress response, effectively resisting catastrophic failure of the overall structure caused by a rapid decrease in stress in practical engineering applications.

[0032] exist Figure 4 In (b), based on the data in Table 1, under the same compression conditions, the unit cell length was uniformly set to L=7mm. For the yield strength of different lattice structures at a relative density of 0.078, the yield strength of the GSIBCC lattice structure was lower than that of OCT, decreasing by 27.37%, but higher than that of BCC, increasing by 17.09% at a relative density of 0.078. Furthermore, the yield strength of GSIBCC was consistently higher than that of the EXBCC-A and EXBCC-B lattice structures. Figure 4 (c) and Figure 4 In (d), the GSIBCC lattice structure exhibits the highest plateau stress and specific energy absorption at a relative density of 0.078. Compared to OCT, the plateau stress of GSIBCC is increased by 99.32%; compared to BCC, its plateau stress is increased by a maximum of 114.94%. Meanwhile, the specific energy absorption of GSIBCC is increased by 99.16% compared to OCT and by 113.83% compared to BCC. In summary, the yield strength of the GSIBCC lattice structure is lower than that of OCT, but its plateau stress and specific energy absorption are significantly enhanced compared to both BCC and OCT.

[0033] Table 1. Compressive mechanical properties of BCC, OCT, EXBCC-A, EXBCC-B and GSIBCC lattice structures

[0034] This invention further provides a method for preparing a self-sensing mechanical metamaterial lattice structure based on the layered characteristics of deep-sea glass sponge, comprising the following steps: Step (a): Based on the MSLA molding principle and process characteristics, a lattice structure sample was prepared using a commercial digital photopolymerization 3D printer (NOVA 3D Bene 4) based on the MSLA principle. The parameters were set as follows: layer height 30~50μm, exposure time 5~8s, bottom layer exposure time 30~60s, lift speed 50~80mm / min, lift height 5~8mm, and printing was performed using flexible LCD photosensitive resin at 20℃~25℃. Step (b): Following the preset three-dimensional model path, the double diagonally reinforced body-centered cubic lattice structure EXBCC and the glass-like sponge body-centered cubic lattice structure GSIBCC are prepared by layer-by-layer exposure and curing with ultraviolet light. Step (c) involves cleaning the printed sample with a 95% alcohol solution for 10-30 minutes to remove any uncured liquid photosensitive resin remaining on the sample surface and inside the pores, thereby further improving the molding quality, mechanical properties, and reliability of the test results of the lattice structure. After thoroughly rinsing with deionized water and drying the surface with a hair dryer, the sample is placed in a UV curing oven for 10-30 minutes for post-curing to obtain the EXBCC and GSIBCC lattice structures. Step (d): Immerse the lattice structure directly into the carbon nanotube conductive solution, place the whole structure in a vacuum pump at a vacuum degree of 0.08~0.09Mpa for evacuation and maintain for 20~30min, and then slowly release the pressure to atmospheric pressure. The carbon nanotube conductive solution is prepared according to the following method: At a mass ratio of (20~30):(0.1~0.3), La33 aqueous binder was added to a single-walled carbon nanotube aqueous dispersion with a carbon nanotube content of 0.4~0.5%. The mixed solution was placed on a room temperature magnetic stirrer and stirred continuously for 6~10 h to obtain a uniformly dispersed and stable carbon nanotube aqueous suspension, which was used as a conductive solution for subsequent impregnation treatment. Step (e) involves allowing the sample to stand in the carbon nanotube suspension for another 2-5 hours, then placing it on a glass plate and drying it together in a drying oven at 50-60°C for 2-5 hours to finally complete the preparation of the EXBCC and GSIBCC self-sensing lattice structures.

[0035] The following examples illustrate the fabrication of the self-sensing biomimetic lattice structure of the present invention.

[0036] Example 1 (a) The parameters were set as follows: layer height 40 μm, exposure time 6s, bottom layer exposure time 60s, lifting speed 70mm / min, lifting height 5mm, and printing was performed using flexible LCD photosensitive resin at 20℃. (b) The double diagonally reinforced body-centered cubic lattice structure EXBCC and the glass-sponge-like body-centered cubic lattice structure GSIBCC were prepared respectively. (c) Clean with 95% alcohol solution for 20 min, rinse with deionized water, blow dry, and place in UV curing oven for 20 min post-curing treatment to obtain EXBCC and GSIBCC lattice structures. (d) The lattice structure was directly immersed in a carbon nanotube conductive solution, and a vacuum of 0.08 MPa was applied and maintained for 25 minutes before the pressure was slowly released to atmospheric pressure. The carbon nanotube conductive solution is prepared according to the following method: La33 aqueous binder was added to a single-walled carbon nanotube aqueous dispersion with a carbon nanotube content of 0.45% at a mass ratio of 25:0.3, and the mixture was stirred at room temperature for 8 h. (e) The sample was left to stand in the carbon nanotube suspension for 3 hours and then dried at 50°C for 5 hours to complete the preparation of the EXBCC and GSIBCC self-sensing lattice structures.

[0037] Example 2 (a) The parameters are set as follows: layer height 30μm, exposure time 8s, bottom layer exposure time 30s, lifting speed 80mm / min, lifting height 6mm, and printing is performed using flexible LCD photosensitive resin at 25℃. (b) The double diagonally reinforced body-centered cubic lattice structure EXBCC and the glass-sponge-like body-centered cubic lattice structure GSIBCC were prepared respectively. (c) Clean with 95% alcohol solution for 30 min, rinse with deionized water, blow dry, and place in UV curing oven for 10 min post-curing treatment to obtain EXBCC and GSIBCC lattice structures. (d) The lattice structure was directly immersed in a carbon nanotube conductive solution, and a vacuum of 0.085 MPa was applied and maintained for 20 min, and then the pressure was slowly released to atmospheric pressure. The carbon nanotube conductive solution is prepared according to the following method: La33 aqueous binder was added to a single-walled carbon nanotube aqueous dispersion with a carbon nanotube content of 0.4% at a mass ratio of 30:0.2, and the mixture was stirred at room temperature for 6 hours. (e) The sample was left to stand in the carbon nanotube suspension for 5 hours and then dried at 55°C for 2 to 5 hours to complete the preparation of the EXBCC and GSIBCC self-sensing lattice structures.

[0038] Example 3 (a) The parameters are set as follows: layer height 50μm, exposure time 5s, bottom layer exposure time 40s, lifting speed 50mm / min, lifting height 8mm, and printing is performed using flexible LCD photosensitive resin at 25℃. (b) The double diagonally reinforced body-centered cubic lattice structure EXBCC and the glass-sponge-like body-centered cubic lattice structure GSIBCC were prepared respectively. (c) Clean with 95% alcohol solution for 10 min, rinse with deionized water, blow dry, and place in UV curing oven for 30 min post-curing treatment to obtain EXBCC and GSIBCC lattice structures. (d) The lattice structure was directly immersed in the conductive solution of carbon nanotubes, and a vacuum of 0.09 MPa was applied and maintained for 30 min, and then the pressure was slowly released to atmospheric pressure. The carbon nanotube conductive solution is prepared according to the following method: La33 aqueous binder was added to a single-walled carbon nanotube aqueous dispersion with a carbon nanotube content of 0.5% at a mass ratio of 20:0.1, and the mixture was stirred at room temperature for 10 h. (e) The sample was left to stand in the carbon nanotube suspension for 2 hours and then dried at 55°C for 4 hours to complete the preparation of the EXBCC and GSIBCC self-sensing lattice structures.

[0039] like Figure 5 As shown, a lattice structure sample is displayed. Figure 5 (a) is a set of lattice structure samples; Figure 5 (b) BCC, OCT, and EXBCC at the same relative density of 0.163 m Individual detailed images of four lattice structures: (=1 / 4), GSIBCC, and others. The unit size L1 is set to 6 mm for all structures, and the overall structure consists of 3×3×3 units arranged periodically along three orthogonal directions. The fabrication process of the carbon nanotube solution-wetted lattice structure is as follows: Figure 6 As shown.

[0040] like Figure 7 As shown, a set of samples after the above-mentioned samples were treated with impregnation of carbon nanotubes are presented. Figure 7 (a) Figure 7 (b) includes BCC, OCT, EXBCC ( m =1 / 4) and GSIBCC, two samples were prepared for each. Figure 8 These are detailed diagrams of the four types of lattice structures. Figure 8 (a) is 200um; Figure 8 (b) is 10µm; Figure 8 (c) is 2µm; Figure 8(d) is 500 nm; it can be roughly observed that the carbon nanotubes are relatively uniformly distributed on the surface of the lattice structure and in the rod connection area, and no obvious local aggregation phenomenon is observed.

[0041] For impact protection of fragile components and wearable devices, this invention combines advanced additive manufacturing technology with the self-sensing monitoring function of the lattice structure provided by carbon nanotubes, to protect EXBCC (Extra-Bioducted Carbon-Based Carbon) from impact. m= 1 / 4) is used as a flexible self-sensing lattice structure in high-altitude falling object buffer protection and elbow protection.

[0042] First, this invention designs an experiment to simulate fragile items under impact load using an egg and an experiment to simulate the vertical free fall of a solid sphere using an egg in order to protect fragile products by buffering and absorbing energy.

[0043] Figure 9 This invention relates to the experimental application of the EXBCC (m=1 / 4) lattice structure under dynamic impact, wherein... Figure 9 (a) and Figure 9 (b) is a schematic diagram of the car impact experiment, in which weights are added inside the car, and its total weight is 1.95 kg. The protective structure consists of a 3D-printed outer protective cover and a flexible dot matrix structure pasted on the outside. An egg is placed inside the protective cover to simulate fragile components, and the flexible dot matrix structure serves both as a buffer and a sensing function. The dot matrix structure is connected to an LCR (Liquid Crystal Resistor) to monitor the resistance of the dot matrix structure in real time during the impact.

[0044] Figure 9 (c) and (d) EXBCCs fitted with wetted carbon nanotubes m The comparison results (1 / 4) of the lattice structure and the sample without the lattice structure show that, after the car's low-speed impact, the egg inside the protective shield did not crack or suffer significant damage, and the overall protective structure remained stable. This indicates that the flexible lattice structure can effectively absorb and dissipate impact energy. In contrast, the control sample without the lattice structure experienced direct impact energy on the egg, causing the shell to crack. Combined with... Figure 10 The electrical test results Figure 10 (a) shows the resistive response of the EXBCC (m=1 / 4) lattice structure during the first impact; Figure 10 (b) shows the resistance response of the lattice structure during the second impact. Analysis of the resistance change rate during the impact process revealed that at the moment the vehicle came into contact with the protective structure, the structure underwent significant structural deformation, and the resistance change rate dropped rapidly, forming a clear peak response.

[0045] Figure 11 This invention relates to an experiment testing the energy absorption of free fall. Figure 11(a) shows a schematic diagram of an experiment on energy absorption by free fall of an egg. The egg is released from a predetermined height (60 cm from the height of the transparent roll) and allowed to fall freely under the influence of gravity. The egg is then placed against a flexible lattice structure EXBCC (…). m A block with a ratio of 1 / 4 collides with a wooden block that has not been fitted with a flexible lattice structure. Figure 11 (b) is the egg falling onto the flexible lattice structure EXBCC ( m =1 / 4) Experimental diagram of the surface and the surface of the wooden block, Figure 11 (c) shows the experimental process. In the control experiment without the flexible lattice structure, the egg collided directly with the surface of the wooden block, causing the local stress to rapidly exceed the eggshell's bearing capacity, resulting in the egg breaking noticeably upon impact. In contrast, when the egg fell onto the surface of the flexible lattice structure, the lattice structure absorbed the impact energy through the deformation of the rods, significantly reducing the instantaneous stress applied to the egg, and the egg did not break.

[0046] Figure 12 This invention relates to the application of the EXBCC (m=1 / 4) lattice structure in elbow pads. Figure 12 (a) is the conductive lattice structure EXBCC ( m =1 / 4) An overall schematic diagram of the elbow brace embedded inside. By actively subjecting the elbow brace to multiple contacts and impacts with the wall, it simulates the external impact loads that the human body may suffer in daily activities or accidents. During the impact, the external impact force first acts on the internally embedded lattice structure. Due to the geometric deformation behavior of this lattice structure, it effectively absorbs and dissipates impact energy when subjected to impact loads, thereby greatly mitigating the damage to the elbow caused by external impacts. Figure 12 (b) shows the electrical response of the lattice structure recorded during multiple elbow impacts. It can be observed that the relative resistance value shows a significant instantaneous change at each impact, clearly identifying and recording different elbow impact events; after the impact ends, the resistance value can gradually recover to the initial level over time, showing good repeatability, indicating that the lattice structure and conductive mesh have not suffered significant irreversible damage and maintain stable sensing capability.

[0047] In summary, embedding conductive lattice structures into wearable protective gear such as elbow pads not only effectively enhances the equipment's mechanical load-bearing capacity, energy absorption, and protective performance, but also enables integrated dual functions of real-time electrical sensing and feedback of external impact loads. The significant change in relative resistance over time reflects not only the structural deformation behavior during impact but also indirectly characterizes the presence of external forces. These results demonstrate that conductive lattice structures have promising application potential in sports protection, intelligent protective gear, and human impact monitoring.

[0048] This invention is not limited to the above embodiments. Based on the technical solutions disclosed in this invention, those skilled in the art can make some substitutions and modifications to some of the technical features without creative effort, and all such substitutions and modifications are within the protection scope of this invention.

Claims

1. A self-sensing biomimetic lattice structure, characterized in that, The lattice structure uses cubic lattice units of their respective configurations as basic lattice structural units, and periodically expands them along the three orthogonal directions of space X, Y, and Z to form a lattice structure of the scale of M×N×P, where M≥1, N≥1, and P≥1. The dot matrix structure unit includes an EXBCC double diagonal reinforced dot matrix unit; the EXBCC double diagonal reinforced dot matrix unit includes a cubic frame composed of outer frame members (1), a pair of diagonal members (3) are connected on the square frame of the top and bottom surfaces of the cubic frame, and a pair of four intersecting members (2) are provided in the cubic frame to connect the pair of diagonal members (3) and the outer frame members (1) respectively. The short diagonal members of the four intersecting members (2) are connected to the intersection of the pair of diagonal members (3), and the long diagonal members of the four intersecting members (2) converge at the nodes that connect to the outer frame members (1).

2. The self-sensing biomimetic lattice structure according to claim 1, characterized in that, The cross member (2) consists of four diagonal members distributed along the outer frame member (1). The cross member (2) splits into two independent cross nodes along the central intersection point. The four cross members (2) are symmetrically offset in both directions along the extension direction of the outer frame member (1).

3. The self-sensing biomimetic lattice structure according to claim 1, characterized in that, One end of the short diagonal bar of the four intersecting members (2) is connected outside the intersection point of a pair of diagonal members (3), and the distance extended inward from the connection point relative to the vertex of the diagonal member (3) is... L1, where L1 is the side length of outer frame member 1, m is the offset coefficient, 0 < m ≤ 1 / 2.

4. The self-sensing biomimetic lattice structure according to claim 1, characterized in that, The four intersecting members (2) have one end of their long diagonal members connected to the longitudinal upright of the outer frame member (1). The connection point is offset by a bidirectional symmetrical amount of mL1 relative to the vertex of the outer frame member (1). L1 is the side length of the outer frame member 1, m is the offset coefficient, and 0 < m ≤ 1 / 2.

5. The self-sensing biomimetic lattice structure according to claim 1, characterized in that, The dot matrix structure unit includes the GSIBCC glass-like sponge dot matrix unit, wherein the GSIBCC glass-like sponge dot matrix unit has a central member (4) distributed between the intersection node of the long diagonal bar of the EXBCC dot matrix unit and the intersection node of the four intersecting members (2).

6. A method for preparing a self-sensing biomimetic lattice structure according to any one of claims 1-5, characterized in that, Includes the following steps: (a) Photosensitive resin is selected as the molding material, photocuring molding process is adopted, surface projection photocuring 3D printing equipment is selected, and flexible LCD photosensitive resin is used for printing. (b) Following the preset three-dimensional model path, the double diagonal reinforced body-centered cubic lattice structure EXBC and the glass-like sponge body-centered cubic lattice structure GSIBCC are printed by setting parameters through layer-by-layer exposure and curing with ultraviolet light. (c) The obtained lattice structure was ultrasonically cleaned with anhydrous ethanol and deionized water, dried, and UV cured to obtain EXBCC or GSIBCC lattice structure. (d) The lattice structure is directly immersed in a carbon nanotube conductive solution, the whole structure is treated under vacuum conditions, and then the pressure is slowly released to atmospheric pressure; (e) The sample was left to stand in the carbon nanotube suspension for a while and then dried to obtain the EXBCC or GSIBCC self-sensing lattice structure.

7. The method for preparing a self-sensing biomimetic lattice structure according to claim 6, characterized in that, In step (a), the parameters are set as follows: layer height 30~50μm, exposure time 5~8s, bottom layer exposure 30~60s, lifting speed 50~80mm / min, lifting height 5~8mm, and printing is performed using flexible LCD photosensitive resin in an environment of 20℃~25℃.

8. The method for preparing a self-sensing biomimetic lattice structure according to claim 6, characterized in that, The carbon nanotube conductive solution is prepared according to the following method: A conductive solution was obtained by adding La33 aqueous binder to a single-walled carbon nanotube aqueous dispersion with a content of 0.4-0.5% at a mass ratio of (20~30):(0.1~0.3) and stirring the mixture.

9. The method for preparing a self-sensing biomimetic lattice structure according to claim 6, characterized in that, In step (c), the lattice structure is ultrasonically cleaned in 95% anhydrous ethanol for 15-30 min; then cured in a UV curing chamber for 10-30 min. In step (d), the treatment is carried out under a vacuum of 0.08~0.09 MPa for 20~30 min; In step (e), the sample is left to stand in a carbon nanotube suspension for 2-5 hours and then dried at 50-60°C for 2-5 hours.

10. The application of the self-sensing bionic lattice structure according to any one of claims 1-5 in fragile devices and wearable devices.